Macroprudential Measures and Taxation in the Housing Markets - Essi Eerola (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
The recent financial crisis and subsequent global recession have been followed by a wave of macroprudential measures in the housing market. At the same time, governments have a long tradition of conducting tax policies which encourage households to acquire owner-housing. These tax advantages may be at least partly responsible for the need to regulate borrowing. In terms of policy, the goal should be to identify instruments that reduce the negative effects of household leverage while minimizing the welfare costs to households. This EconPol policy brief examines the joint effects of the tax system and credit regulation. The recent financial crisis and subsequent global recession have been followed by a wave of macroprudential measures in the housing market. At the same time, governments have a long tradition of conducting tax policies which encourage households to acquire owner-housing. These tax advantages may be at least partly responsible for the need to regulate borrowing. In terms of policy, the goal should be to identify instruments that reduce the negative effects of household leverage while minimizing the welfare costs to households. Therefore, it seems important to look into the joint effects of the tax system and credit regulation.
Keywords: 330